2022
DOI: 10.4049/jimmunol.2100824
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell–Based High-Throughput Ig and TCR Repertoire Sequencing Analysis in Rhesus Macaques

Abstract: Recent advancements in microfluidics and high-throughput sequencing technologies have enabled recovery of paired H and L chains of Igs and VDJ and VJ chains of TCRs from thousands of single cells simultaneously in humans and mice. Despite rhesus macaques being one of the most well-studied model organisms for the human adaptive immune response, high-throughput single-cell immune repertoire sequencing assays are not yet available due to the complexity of these polyclonal receptors. We used custom primers that ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…γδ T cells are attractive candidates for novel vaccines against TB because they are not MHC I restricted, and thus, can be broadly stimulated in the target population ( 15 ). Early studies identified simple phosphoantigens such as isopentenyl pyrophosphate (IPP) as potent polyclonal stimulators of virtually all γ 9 δ 2 T cells ( 16 ). However, our previous studies have shown that only a subset of the IPP or other phosphoantigen-responsive γδ T cells expressing a more limited diversity of γδ TCR, are capable of recognizing Mtb-infected human monocytes and mediating inhibitory effects on intracellular mycobacteria ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…γδ T cells are attractive candidates for novel vaccines against TB because they are not MHC I restricted, and thus, can be broadly stimulated in the target population ( 15 ). Early studies identified simple phosphoantigens such as isopentenyl pyrophosphate (IPP) as potent polyclonal stimulators of virtually all γ 9 δ 2 T cells ( 16 ). However, our previous studies have shown that only a subset of the IPP or other phosphoantigen-responsive γδ T cells expressing a more limited diversity of γδ TCR, are capable of recognizing Mtb-infected human monocytes and mediating inhibitory effects on intracellular mycobacteria ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis of these primers shows them to be suitable for enrichment of TRA and TRB genes from rhesus macaques, and therefore this set of primers can be used for both species of macaques [ 25 ]. Similarly, nested primers for rhesus TCR enrichment using the 10X Genomics platform can also be used for cynomolgus macaques as the regions to which they anneal are 100% conserved [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%